Feeding difficulties in infancy as an early symptom of different forms of diabetes insipidus – a series of cases - Banasiak, Katarzyna Anna; Stańczyk, Małgorzata Barbara; Szczepanik, Elżbieta; Krawiranda, Katarzyna Monika; Janus, Anita; Kościelny, Kacper Piotr; Tkaczyk, Marcin (Pediatria Polska - Polish Journal of Paediatrics, 2024)
Feeding disorders of infancy are common in paediatric practice. Among rare causes of this disturbance is diabetes insipidus (DI), which is a clinical syndrome characterized by polyuria, polydypsia and dehydration with hypernatraemia. Central diabetes insipidus (CDI, vasopressin deficiency) is more common in children than nephrogenic diabetes insipidus (NDI, an inability to respond adequately to vasopressin). Regardless of the type of DI, the main goal of treatment is to decrease thirst and urine output and achieve proper ion and fluid balance. We present three cases of infants with feeding difficulties. The first two cases concerned patients with semilobar holoprosencephaly (HPE). Their stories show the importance of knowing the most common abnormalities associated with HPE, such as CDI. The third child had similar problems with feeding which resembled a defect of the central nervous system, but was finally diagnosed as NDI. The diagnostic and therapeutic approach is demonstrated in the paper with special regards to safe management of hypernatraemic dehydration.